A race for maintaining personal data - how to manage consumers´ data under the right to be forgotten and the right to data portability of the new EU GDPR - Vale, Alexandre Soares de Oliveira Lucena e (2018)
The phenomenon of Big Data is revolutionizing business and imposes the study of two underlying issues: data protection and economic value of personal data. With the new EU Data Protection Regulation, the use of personal data by corporations has become more limited, giving individuals the right to ask from companies to delete their personal data or transfer it to other competitors. Under these conditions, this preliminary study explores how individuals in the European Union view their new data protection rights and whether they put a price on their privacy, showing that a significant number is willing to make trade-offs.